The correlation between the Leadership Style of the Room Head with Nurse Performance at Medical Surgery Room, Dirgahayu Hospital Samarinda 2016 - Edy Mulyono; Amin Huda Nurarif; Bertin . (ITKES Wiyata Husada Samarinda, 2016)
Leadership style is the reflection of a leader’s behavior that relates to his capability in holding the leadership. Four famous styles of leaderships are Autocratic, Democratic, Participative, and Laizzes-faire. Leadership style affects much on nurse performance that determines the nurse service quality. The nurse performance is a nurse’s activity in implementing a duty obligation and responsibility to reach the profession objective to give nursing guidance. So that it aims to know the relationship between the leadership style of the room head and the nurse performance in a medical surgery room, Dirgahayu Hospital, Samarinda. The Method is the total population of nurses at the medical surgery room, Dirgahayu Hospital, Samarinda was 114 and the total sample was 68 nurses. The research design used in this research was analytical comparative research with cross sectional approach. The level significant was 95% (a= 0.05). The result of the research revealed that there was a relationship between the leadership style of the room head and the nurse performance in a medical surgery room. The result of using Chi-square statistic test got p-value of 0.009, and P value was smaller than alpha value, 0.05. Conclusion: Therefore, Ha was accepted and Ho was rejected. In other words, there was a relation between the leadership style of the room head with nurse performance in medical surgery room, Dirgahayu Hospital, Samarinda. The room head should be optimal in the implementation of leadership style in order to improve the room nurse performance. They should give nursing guidance to the patients and their family, so that they were able to improve the nursing service quality that affected the BOR (Bed Occupancy Ratio) enhancement.